Physico-chemical characterization of Al2O3/Ti6A4V type thermal barrier systems - Djamel Amari; Khaoula Rahmouni; Nadia Saoula; Hafit Khireddine; Youcef Khelfaoui (Revue des Énergies Renouvelables)
Al2O3 alumina deposits were deposited on Ti6A4V titanium alloy substrates by rf-PVD at different substrate polarizations 0V, -50V, -100V and without polarization (wp). SEM images, at the surface of the deposits, showed a very good substrate coverage with a dense morphology. Quantitative EDS analysis of these deposits revealed the presence of the elements Al and O in these deposits. The mass percentage of these elements, at different polarizations of the substrate, varies between 51.72% and 56.19% for Al and between 43.80% and 48.27% for O. The images, revealed by AFM, showed well-spread deposits on the surface of the substrates with relatively uniform grooves. The values of the arithmetic roughness Ra, ranging from 3.45 to 4.75 nm, testify to the low crystallinity of these deposits and an appreciable density. The DRX of these deposits in mode showed a weak crystallization of the Al2O3 phase and characteristic peaks of the partially crystallized phases Al0.3Ti1.7, and Ti0.7V0.3, resulting from the interaction of the elements of the Ti6A4V substrate and those of the Al2O3 deposit.